Factors influencing the episode duration and the anatomical and functional outcome in cases of acute central serous chorioretinopathy. Issue 1 (1st December 2020) - Parajuli, Anil; Joshi, Purushottam
Abstract : Objective: To investigate the factors affecting the duration of subretinal fluid (SRF) resolution and their correlation with the final anatomical and functional outcome in cases of treatment naïve acute central serous chorioretinopathy (CSCR). Methods and analysis: We retrospectively studied 93 eyes of 93 patients diagnosed with treatment naïve acute CSCR presenting within 30 days of onset of symptoms. The eyes were divided into two groups (1 and 2) based on the duration of SRF resolution; which was ≤3 months in group 1 and >3 months in group 2. Demographic and medical history, and spectral domain optical coherence tomography features were noted and their association with duration for SRF resolution, final central macular thickness (CMT) and final best-corrected visual acuity (BCVA) were studied. All the patients were prescribed topical non-steroidal anti-inflammatory drug for 1 month at the diagnosis of CSCR. Results: Longer duration of symptoms, female gender and baseline OCT factors like hyper-reflective dots and retinal pigment epithelial bumps were associated with longer duration for SRF resolution (p<0.001, p=0.04, p=0.001 and p=0.01, respectively). The SRF resolution time had strong correlations with the final CMT (r=−0.589, p<0.001) and final BCVA in logarithm of minimum angle of resolution (LogMAR) (r=+0.599, p<0.001). Group 2 eyes had worse final BCVA and thinner final CMT than Group 1 (both p<0.001). The final CMT of the patients of Group 1 was statistically thinner than the normal population (p<0.001). Conclusion: Patient's baseline clinicodemographic and OCT features can be used to predict the course and visual outcome in cases of treatment naïve acute idiopathic CSCR.